Factors and mechanisms of archaeal transcription termination and DNA repair - Marshall, Craig, author; Santangelo, Thomas J., advisor; Peersen, Olve, committee member; Wilusz, Carol, committee member; Yao, Tingting, committee member (Colorado State University. Libraries, 2022)
RNA synthesis by RNA polymerase (RNAP) is an essential process and must be properly regulated both temporally and spatially to ensure cellular health in dynamic environments. Regulation of RNA synthesis in response to internal and environmental stimuli is typically achieved through interactions with RNAP at all stages of the transcription cycle- initiation, elongation, and termination. While studies of transcription initiation and elongation have identified multiple regulatory transcription factors and defined mechanisms, only a handful of protein factors able to terminate transcription have yet been described, and the general mechanism of transcription termination is still highly debated. We previously identified the first two factors capable of terminating transcription elongation complexes (TECs) in Archaea from the genetically tractable Thermococcus kodakarensis, and use both factors as models to explore the molecular mechanisms involved in collapse of the TEC. The Factor that terminates transcription in Archaea (FttA), a close homolog of the human CPSF subunit CPSF73, is completely conserved throughout Archaea, and appears to act analogously to the bacterial termination factor Rho, terminating transcription after the uncoupling of transcription and translation at the end of protein coding genes. We employed a novel genetic screen to verify the role of FttA in the polar repression of transcription, a phenomenon specific to regulation of genes contained within operons in prokaryotes. Eta, a euryarchaeal-specific superfamily 2 (SF2) helicase, appears to terminate transcription in a more specialized context, potentially terminating transcription of TECs arrested at sites of DNA damage while concurrently recruiting appropriate DNA repair enzymes, akin to the bacterial termination factor Mfd. A structure-function study of Eta employing select mutations derived from a crystallographic structure was conducted to elucidate the Eta-TEC contacts and various activities of Eta required for Eta-mediated termination. Further, many efforts were directed at establishing a role of Eta as an archaeal transcription-repair coupling factor (TRCF), and while this was not achieved, a state-of-the-art next-generation sequencing based approach to monitor nucleotide excision repair (NER) and the sub pathway transcription-coupled repair (TCR) genome-wide was developed and verified in E.coli. The work in this dissertation adds valuable insight to multiple fields of research. First, exploration into the mechanism of Eta-mediated transcription termination reveals a potential shared susceptibility of core RNAP subunits to transcription termination while elucidating activities of SF2 helicases- enzymes which are ubiquitously distributed in multiple essential cellular pathways. Second, our genetic screen identifies FttA as the archaeal polarity factor, shedding light on functions of an ancestral factor indispensable in mammalian transcription termination pathways. Establishment of the novel RADAR-seq/RNA-seq measurement of NER genome-wide will likely prove instrumental in future studies of archaeal DNA repair, and potentially presents a new paradigm in research of eukaryotic-like NER by use of Archaea as a advantageous model organism.